Slaying Excel dragons : a beginners guide to conquering Excel's frustrations and making Excel fun - Girvin, Mike (Holy Macro! Books, 2011)
"Provides information on efficiently creating Excel reports, covering such topics as keyboard shortcuts, style formation, formulas and functions, data analysis, charts, and conditional formatting."